An examination of speech characteristics under conditions of affective reactivity and variable cognitive load as distinguishing feigned and genuine schizophrenia - Najolia, Gina M. (2013)
Proper assessment of schizophrenia is complicated by the need for clinicians to be cognizant of the possibility of malingering, i.e., the intentional production of false or grossly exaggerated symptoms, motivated by external incentives. Current standardized schizophrenia malingering detection methods rely on endorsement of improbable or exaggerated, mainly positive, symptoms. However, these detection methods may be vulnerable to successful manipulation by sophisticated malingerers, particularly if coached regarding response style assessment strategies. This paper explored the utility of supplemental variables to examine in schizophrenia malingering detection by using a simulation study design to compare schizophrenia patients, a community participant sample instructed to feign schizophrenia symptoms, and an honest responder control group on behavioral speech characteristics indicative of thought disorganization (i.e., referential disturbances) and negative symptoms (i.e., alogia and flat affect) under experimentally-manipulated conditions of affective reactivity and cognitive load. Results indicated that the feigning group was distinguishable from the schizophrenia group based on differences in magnitude of speech disorganization during conditions of affective reactivity, due to feigners’ inability to mimic the schizophrenia group’s referential failures, and in magnitude of flat affect during conditions of affective reactivity and cognitive load, due to feigners’ excessively impaired use of formant inflection (i.e., vocal inflection related to tongue movement). Feigning and schizophrenia groups were also distinguishable due to feigners’ excessive impairment in cognitive task performance, observed both in group comparisons and differential patterns of change in cognitive task accuracy across cognitive load conditions